Evaluation of the regenerative potential of decellularized skeletal muscle seeded with mesenchymal stromal cells in critical-sized bone defect of rat models - Lujain hakeem; Mohammed Al-Kindi; Nihal AlMuraikhi; Sarah BinHamdan; Ahmad Al-Zahrani (Elsevier, 2021)
Background: The morbidities and complications reported in the reconstruction of large bony defects have inspired progression in the field of bioengineering, with a recent breakthrough for the use of decellularized skeletal muscle grafts (DSMG). Aim: To assess the osteogenic potentials of seeded DSMG in vitro and to investigate bone regeneration in critical size defect in vivo. Materials and Methods: Assessment of cell viability and characterization was carried out on seeded DSMG for different intervals in vitro. For in vivo experiments, histological analysis was performed for rat cranial defects for the following groups: (A) non-treated DSMG and (B) seeded DSMG after a period of 8 weeks. Results: The in vitro experiment demonstrated the lack of cytotoxicity and inert properties of seeded DSMG; these facilitated the osteogenic differentiation and significant gene expressions, particularly of COL1A1, RUNX2, and OPN (1.9174 ± 0.11673, 1.1806 ± 0.02383, and 1.1802 ± 0.00775, respectively). In the in vivo experiment, superior results were detected in the seeded DSMG group which showed highly vascularized and cellular dense connective tissue with deposited bone matrix and multiple scattered islets of newly formed bone. Conclusion: Our results demonstrated the promising aspects of DSMG; however, there is a lack of studies to support further implications.